Reduction of discrete algebraic riccati equations: Elimination of generalized eigenvalues on the unit circle - Ferrante, A.; Ntogramatzidis, Lorenzo (2018)
The purpose of this paper is to introduce a two-stage procedure that can be used to decompose a discrete-time algebraic Riccati equation into a trivial part, a part that is entirely arbitrary, and a part that can be obtained by computing the set of solutions of a reduced-order Riccati equation whose associated symplectic pencil has no generalized eigenvalues on the unit circle.